What Goes Up, Shouldn't Come Down: Learning from Construction and Engineering Failures - Love, Peter; Lopez, Robert; Goh, Yang Miang; Tam, C. (Elsevier, 2011)
Design errors can severely jeopardize safety and contribute to failures in construction and engineering projects. Such failures can have devastating economic, environmental and social consequences. Significant efforts have been made to reduce the incidence of failures through learning from previous disasters and events by modifying building and engineering codes and standards accordingly. Design errors, however, remain an innate feature of construction and engineering projects. Most errors are identified during construction and require rework, but there is always a potential for some to remain undetected and contribute to failure, and as a result potentially contribute to accidents and loss of life. This paper examines the circumstances and issues that contributed to a series of construction and engineering failures, to enable development of a systemic learning framework to contain and reduce design errors and potential failures and accidents.